DAMPAK PENGGUNAAN HANDPHONE TERHADAP AKTIVITAS BELAJAR SISWA SEKOLAH DASAR - Satrianawati, Satrianawati (Universitas Muhammadiyah Surakarta, 2017)
This research aims to show the impact of using handphone in learning activities of students in elementary school. This research is a descriptive qualitative research. The data source in this study are teachers, parents, and students. The data was collected by using the techniques of observation, interviews, and documentation. The results showed that children using handphone tend to be lazy to learn and love the instant ways in resolving problems. The children with the level of interaction with the handphone for more than three hours per day tend to be lazy and not paying attention to the lesson.